Interp.reter$1 (Bs thematic dictionary :s nterp.reter$1 (Bs thematic dictionary : p.olitical, dip.lomatic, scientific, technical, medical, accounting, commercial, economic, financial, military, legal and Islamic studies exp.ressions : English-Arabic, with general English-Arabic & Arabic-English indices /s - (3MSjfs (Liban : Librarie du Liban p.sblishers, 2005)
(3deQI GdGhdi jdbi GdeJQLe GdahQj(B/(3GdeJQLeI GdahQjI Qgf JUQag (B.(3eYLeG ehVhYjG ddJQLeI GdahQjI jJfGhd eNJda GdMbhd GdeSJNOeI hgh jJhLg Gdi GdeJQLejf GdahQjjf GdYQH hZjQ GdYQH GdPjf jMJGLhf Gdi eSGQO ehVhYjI hTQhM JSge aj JSgjd egeJge hJfejI egGQGJge(B. (3jSJLjH eYLe GdJQLeI GdahQjI GdehVhYj Gdi GdMGLGJ GdGcGOjejI, ceG jSJLjH Gdi VQhQGJ GdShb GdedMI ajZOh YhfG ddeJQLe aj TJi GdeLGdGJ(B. (3hgh aj GdGUd MUjdI KdGKI YbhO ef GdNHQI GdTNUjI aj GdJQLeI GdcJGHjI haj GdJQLeI GdahQjI, hCjVG aj JYdje gGJjf GdeGOJjf(B. (3JQJcR eSGQO GdeYLe GdehVhYjI aj ZGdHjJgG Ydi GdJYGHjQ GdGfcdjRjI GdeJOGhdI aj Mbd GdJQLeI GdahQjI, hefgG GdJYGHjQ GdSjGSjI hGdOHdheGSjI hGdYdejI hGdafjI hGdWHjI hGdeMGSHjI hGdJLGQjI hGdGbJUGOjI hGdeGdjI hGdYScQjI hGdbGfhfjI hGdOQGSGJ GdGSdGejI hZjQgG(B. (3hHGdGVGaI Gdi GdeYGLe GdGfcdjRjI GdYQHjI hGdYQHjI GdGfcdjRjI aGf GdeDda bO GSJfO Gdi eQGLY bjeI aj hVYg gPG GdeYLe, efgG GdUMa GdGfcdjRjI, hTQYI GdGee GdeJMOI, hbQGQGJ eLdS GdGef, hGdGJaGbGJ GdOhdjI, heUGOQ CNQi gGeIs
Keywords: DIp.LOMATIC; SCIENTIFIC; TECHNICAL; p.OLITICAL